2015
DOI: 10.1042/bsr20150065
|View full text |Cite
|
Sign up to set email alerts
|

HMA6 and HMA8 are two chloroplast Cu+-ATPases with different enzymatic properties

Abstract: In Arabidopsis chloroplasts, HMA8, the thylakoid Cu+-ATPase and HMA6, the envelope Cu+-ATPase, have different enzymatic properties. These differences might be related to the electrostatic properties of the Cu+ release cavities of the transporters or the nature of their Cu acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
(93 reference statements)
0
25
0
1
Order By: Relevance
“…As shown in Fig. 5A, all mutants are expressed in intracellular structures similar to the ones described for HMA6 (9). Critically, the addition of GFP has no impact on the phenotype because copper MICs of strains expressing either the mutant or mutant-GFP fusion are identical (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…As shown in Fig. 5A, all mutants are expressed in intracellular structures similar to the ones described for HMA6 (9). Critically, the addition of GFP has no impact on the phenotype because copper MICs of strains expressing either the mutant or mutant-GFP fusion are identical (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…form of these ATPases induces growth arrest provided that the transported metal is present in the culture medium at the adequate concentration. We have shown that, for HMA6 and HMA8, the phenotype is linked to the localization of the transporters at the ER membrane and toxic accumulation of metal in this compartment (9). The case of HMA6 is particularly illustrative: expression of the active form of the transporter induces yeast growth arrest at 0.5 mM copper, whereas a strain expressing HMA6-AKT (an inactive form of HMA6 mutated in the phosphorylation site) tolerates up to 1.4 mM copper (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations